Lack of association between the A118G polymorphism of the mu opioid receptor gene (OPRM1) and opioid dependence: A meta-analysis - Janet K Coller; Julia Beardsley; James Bignold; Yibai Li; Florence Merg; et al (Dove Medical Press, 2009)
Janet K Coller1, Julia Beardsley1, James Bignold1, Yibai Li1, Florence Merg1, et al1Discipline of Pharmacology, School of Medical Sciences; 2Discipline of Public Health, School of Population Health and Clinical Practice; 3School of Biomedical and Molecular Science, University of Adelaide, Adelaide, Australia; 4Department of Anatomy and Developmental Biology, Monash University, Melbourne, Australia; 5Division of Craniofacial Medicine, Department of Pediatrics, University of Washington, Seattle, USAAbstract: Mu opioid receptor (OPRM1) gene variants, particularly the common A118G single nucleotide polymorphism (SNP), are among the most frequently studied candidate genes associated with opioid dependence. However, despite numerous case-control studies and meta-analyses, no definitive conclusion has been reached regarding the association of the A118G SNP and risk of developing opioid dependence. This study aimed to resolve this discrepancy by reinvestigating the association between A118G SNP allelic, and for the first time, genotype frequencies and opioid dependence. A meta-analysis of sixteen case-control studies of opioid dependence was performed with a total of 5169 subjects. No association between the A118G allele (P = 0.23) and genotype (P = 0.34) frequencies and opioid dependence was found. However, significant heterogeneity between studies precluded highly definitive conclusions. In addition, the possibility that other OPRM1 SNPs albeit rarer may influence the risk of opioid dependence remains to be investigated at this level. Nonetheless, despite no  evidence of a direct association with risk of dependence, A118G may still influence the pharmacological response to opioids impacting on an individual’s dosage requirements.Keywords: mu opioid receptor, opioid dependence, A118G genotype, meta-analysis